2014
DOI: 10.1089/ars.2013.5437
|View full text |Cite
|
Sign up to set email alerts
|

Fus1/Tusc2 Is a Novel Regulator of Mitochondrial Calcium Handling, Ca2+-Coupled Mitochondrial Processes, and Ca2+-Dependent NFAT and NF-κB Pathways in CD4+T Cells

Abstract: Our findings suggest that Fus1 achieves its protective role in inflammation, autoimmunity, and cancer via the regulation of mitochondrial calcium and calcium-coupled parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
105
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(109 citation statements)
references
References 70 publications
4
105
0
Order By: Relevance
“…Ϫ/Ϫ CD4 ϩ T cells, activation of the NF-B pathway is prominent at a basal level that we associated with a perturbed mitochondrial Ca 2ϩ homeostasis and other coupled mitochondrial parameters in these cells (30).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Ϫ/Ϫ CD4 ϩ T cells, activation of the NF-B pathway is prominent at a basal level that we associated with a perturbed mitochondrial Ca 2ϩ homeostasis and other coupled mitochondrial parameters in these cells (30).…”
Section: Discussionmentioning
confidence: 62%
“…Calprotectin plays an important role in defense against A. baumannii infection through chelation of nutrient Mn and Zn (19). We also showed recently that expression of S100A8 and S100A9, the components of calprotectin complex, is 3-fold higher in Fus1 Ϫ/Ϫ T cells than in Fus1 ϩ/ϩ cells (30). Interestingly, while other groups have shown that in WT C57BL/6 mice IL-17 does not play a significant role in defense against A. baumannii infection, we have shown significant upregulation of IL-17 in Fus1 Ϫ/Ϫ mice after A. baumannii intranasal challenge.…”
Section: Discussionmentioning
confidence: 79%
“…Aging is itself related to the production of free radicals and it has been proposed that excess of free radicals may contribute to amyloid beta aggregation (Christen, 2000). In the present work, we introduce the Fus1 KO mouse as a novel model for sAD that combines premature aging, chronic oxidative stress due to high ROS production and inadequate anti-oxidant machinery, mitochondrial dysfunction, low grade chronic inflammation and aberrant acute inflammatory response (Ivanova et al, 2007; Uzhachenko et al, 2012, 2014; Hood et al, 2013). This model is highly relevant to sAD as increased ROS generation and oxidative damage occur early in the progress of sAD.…”
Section: Discussionmentioning
confidence: 99%
“…Fus1 is involved in regulation of inflammatory and stress responses to various stimuli, infection agents and tumor growth (Hood et al, 2013; Yazlovitskaya et al, 2013, 2015). Fus1 deficient mice display signs of chronic inflammation including increased cytokine production, NF-κB activation and increased levels of ROS (Uzhachenko et al, 2012, 2014). Inflammation leading to ROS production, one of the causative factors of aging, has been shown to reduce expression of Fus1.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of Fus1 results in an autoimmune-like syndrome with chronic inflammation and the spontaneous formation of both vascular tumors and lymphomas. Recent studies have shown that Fus-1 plays important roles in carcinogenesis [29]. The Fus-1 3′ UTR includes a potential target sequence of miR-378 in nucleotides 748-770.…”
Section: Introductionmentioning
confidence: 99%